ENVIRONMENTAL ACCOUNTING FOR THE MANAGEMENT OF CORPORATE SOCIAL RESPONSIBILITY PT.GARAM KALIANGET - Marlina, Desy; syahril (Sekolah tinggi ilmu ekonomi pemuda, 2022)
Environmental Accounting is the policy of incorporating environmental costs into the business practices of companies or government agencies. Corporate Social Responsibility (CSR) is a transparent and ethical behavior that supports the welfare of the community and the environment, which is integrated or applied through social activities within the organization. This research was conducted at PT. Garam (Persero) Kalianget by using Karanganyar village as one of the clarification villages as recipients and managers of CSR provided by PT. Garam (Persero) Kalianget. The results showed the application of environmental accounting at PT. Garam (Persero) Kalianget. good and optimal, this can be seen from the results of the analysis carried out by researchers using 4 aspects of environmental accounting that have been carried out well and also in the disclosure of realized costs is very transparent. For waste management, PT. Garam (Persero) Kalianget has met the feasibility standard.